Cellular MgAl2O4 spinels prepared by reactive sintering of emulsified suspensions - Vitorino, N.
Emulsification of mixed precursor powder mixtures (Al2O3+MgCO3) and subsequent reactive firing were, for the first time, combined to prepare single phase cellular MgAl2O4 and corresponding MgxAl3-xO4 spinels with deviations, from ideal stoichiometry. Suspensions with 50% v/v solid load were emulsified in melted paraffin, with collagen additions to assist consolidation by gelcasting. Early burnout stages and firing conditions were adjusted to avoid collapse of green bodies on heating and to induce favorable microstructural changes, with emphasis on porosity and percolation. (C) 2015 Elsevier B.V. All rights reserved.